Analisis perencanaan dan pengendalian biaya operasional serta pendapatan operasional dalam meningkatkan laba pada The White House Hotel Manado - Mokorimban, Vanisa; Rondonuwu, Sintje; Pinatik, Sherly (Yayasan Widyantara Nawasena Raharja, 2025)
This study analyzes the planning and control of operational costs and revenues to enhance profitability at The White House Hotel Manado. Employing a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation related to the hotel’s financial and managerial operations. The findings indicate that comprehensive cost planning and effective control mechanisms significantly contribute to maintaining operational efficiency and profit growth. However, inefficiencies remain in labor, utilities, and material costs due to limited coordination across departments. The study highlights the synergy between cost management and revenue optimization as a key determinant of profitability. This research contributes to managerial accounting literature by offering empirical insights into how cost planning and control strategies can support sustainable profitability in medium-scale hotels. The novelty of this study lies in its focus on the integrated relationship between cost control practices and revenue performance within the hospitality industry.